6x-(5x-5)=-8-2(x+12)

Simple and best practice solution for 6x-(5x-5)=-8-2(x+12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-(5x-5)=-8-2(x+12) equation:


Simplifying
6x + -1(5x + -5) = -8 + -2(x + 12)

Reorder the terms:
6x + -1(-5 + 5x) = -8 + -2(x + 12)
6x + (-5 * -1 + 5x * -1) = -8 + -2(x + 12)
6x + (5 + -5x) = -8 + -2(x + 12)

Reorder the terms:
5 + 6x + -5x = -8 + -2(x + 12)

Combine like terms: 6x + -5x = 1x
5 + 1x = -8 + -2(x + 12)

Reorder the terms:
5 + 1x = -8 + -2(12 + x)
5 + 1x = -8 + (12 * -2 + x * -2)
5 + 1x = -8 + (-24 + -2x)

Combine like terms: -8 + -24 = -32
5 + 1x = -32 + -2x

Solving
5 + 1x = -32 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
5 + 1x + 2x = -32 + -2x + 2x

Combine like terms: 1x + 2x = 3x
5 + 3x = -32 + -2x + 2x

Combine like terms: -2x + 2x = 0
5 + 3x = -32 + 0
5 + 3x = -32

Add '-5' to each side of the equation.
5 + -5 + 3x = -32 + -5

Combine like terms: 5 + -5 = 0
0 + 3x = -32 + -5
3x = -32 + -5

Combine like terms: -32 + -5 = -37
3x = -37

Divide each side by '3'.
x = -12.33333333

Simplifying
x = -12.33333333

See similar equations:

| 5*2=9-1 | | -4c+8=-4c+8 | | 5(2x+6)-2x=8(x+5) | | -4/17(17/8) | | -5(-2-8m)=10+5m | | x+3=1.34x | | 45+13x=4x+9(5+x) | | 2a-4+-3-7= | | 8n(3n+8)= | | S-7=-10 | | 7/8y=-21 | | 11/9=21-15 | | -8z+12=60 | | c^2+18c+81-q^2= | | 8=m/-3 | | 76=-9k+4 | | -2(v-2)=-3-2v | | 6+5a-122(6+84-6x)-75*45x= | | 11c+6whenc=-3 | | 3(6x-4)+2(3x-3)= | | bx+6=dx+3 | | Sinx=14/23 | | 1=y-(3/2)x | | 3tanx-3=5tanx | | 36+8x=5(5x-5)-7 | | y/3=69 | | 8x+2(-5x-4)=-12 | | w/2=44 | | 360=16x-4+16x-4+14x+34+14x+34 | | 12x+9=75 | | -120=-12x | | 5x-12.3=2x+9 |

Equations solver categories